Anaerotruncus massiliensis sp. nov., a succinate-producing bacterium isolated from human stool from an obese patient after bariatric surgery. (May 2019) - Togo, A.H.; Diop, A.; Dubourg, G.; Khelaifia, S.; Richez, M.; Armstrong, N.; Maraninchi, M.; Fournier, P.-E.; Raoult, D.; Million, M.
Abstract: A new bacterium, strain AT3 T, was isolated by microbial culturomics from a faecal sample from a Frenchman after bariatric surgery. The isolate exhibited 96.6% 16S ribosomal RNA gene nucleotide sequence similarity with Anaerotruncus colihominis strain WAL 14565 T = CCUG 45055 T = CIP 107754 T . Phenotypic and genomic characteristics showed that the new strain represents a novel species, for which the name Anaerotruncus massiliensis sp. nov. is proposed. The type strain is strain AT3 T = CSUR P2007 T = DSM 100567 T .